2023
DOI: 10.3390/ma16062143
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated versus Slow In Vitro Aging Methods and Their Impact on Universal Chromatic, Urethane-Based Composites

Abstract: Structural coloring of dental resin-based composites (RBC) is used to create universal chromatic materials designed to meet any aesthetic need, replacing the mixing and matching of multiple shades. The microstructural adjustments to create this desideratum involve nanoscale organic–inorganic core–shell structures with a particular arrangement. The generally higher polymer content associated with these structures compared to universal chromatic RBCs colored by pigments, which in their microstructure come close … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
(56 reference statements)
0
3
0
Order By: Relevance
“…In view of this discussion, the solutions used for accelerated aging in the present study were selected as suggested in previously published studies, namely the acidic solution with a pH of 4.0 [ 27 , 37 ], the alkaline solution with a pH of 13 [ 34 ], and 75% ethanol [ 38 ]. The most severe deterioration in macro-mechanical properties was observed for the self-cured specimens immersed in ethanol, with FS values 17.9–36.4% lower and FM values 14.7–41.0% lower than the corresponding values measured in the neutral solution.…”
Section: Discussionmentioning
confidence: 99%
“…In view of this discussion, the solutions used for accelerated aging in the present study were selected as suggested in previously published studies, namely the acidic solution with a pH of 4.0 [ 27 , 37 ], the alkaline solution with a pH of 13 [ 34 ], and 75% ethanol [ 38 ]. The most severe deterioration in macro-mechanical properties was observed for the self-cured specimens immersed in ethanol, with FS values 17.9–36.4% lower and FM values 14.7–41.0% lower than the corresponding values measured in the neutral solution.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the specimens were immersed in distilled water. However, different storage media, such as water [58], artificial saliva [59], 75% ethanol/water [47], ethanol [60], and sodium chloride [61], have been employed in previous investigations to evaluate sorption evaluation and to simulate some conditions of the oral cavity. Several studies showed that the type of medium and storage time can affect the degree of sorption [47,58,62].…”
Section: Discussionmentioning
confidence: 99%
“…One of the tests that is performed is artificial aging, which should mimic the oral cavity conditions [10]. Two main methods of artificial aging are possible: thermocycling and the use of water or artificial saliva immersion in time [11,12]. For this reason, we decided to subject the chosen material to unfavorable conditions.…”
Section: Introductionmentioning
confidence: 99%